Mechanisms of transplacental transport and barrier of polybrominated diphenyl ethers: A comprehensive human, Sprague-Dawley rat, BeWo cell and molecular docking study. (1st February 2021) - Yu, Yingxin; Li, Xiaojing; Hu, Junjie; Jiang, Zi'an; Zhang, Xiaolan; Li, Guiying; Ma, Shengtao; Lei, Bingli; Fang, Xiangming; Fan, Ruifang; An, Taicheng
Abstract: Although studies have reported that polybrominated diphenyl ethers (PBDEs) can transfer from mothers to fetuses, the underlying transplacental transport and barrier mechanisms are still unclear. Therefore, we conducted a series of comprehensive experiments in humans, Sprague-Dawley rats, and a BeWo cell monolayer model, as well as a molecular docking study. PBDEs in mothers can transfer to fetuses with a ratio of approximately 0.46, suggesting that the placenta could not efficiently acts as a barrier to PBDE transplacental transport. Similar results were observed in pregnant rats, although varying times were required for different congeners to reach a steady-state in fetuses. The transport ratios at pregnancy day 14 in rats were generally higher than those at pregnancy day 18, which demonstrated that the barrier capacity of immature placentas was lower than that of mature placentas. None concentration-dependent transplacental transport was observed in BeWo cells with efflux ratios of 1.73–2.32, which suggested passive diffusion mechanisms govern the influx of PBDEs through placenta. The accumulated ratios of PBDEs and the inhibitor assay indicated that the effluent channel of P-glycoprotein was partially inhibited by PBDEs. Using molecular docking studies, three pocket sites were identified for different congeners in P-glycoprotein, which demonstrated that the inhibition of P-glycoprotein efflux pump through the pocket sites. Graphical abstract: Image 1 Highlights: The underlying transplacental transport and barrier mechanisms were investigated. Placenta can act as a barrier to PBDE transport, while the efficiency is limited. The barrier capacity of immature placentas was lower than that of mature placentas. Passive diffusion mechanisms govern the transplacental transport of PBDEs. The efflux of PBDEs was inhibited by P-glycoprotein through three pocket sites. Abstract : The article provides comprehensive insights into the underlying transplacental transport and barrier mechanisms of organic contaminants for the first time.